建構社區文化圖像之藝術行動課程：「行動學習」導向在大學通識藝術教育上的應用 Art Action Programs that Establish Community Cultural Image: Application of "Action Learning" to Art Curriculum Programs in Liberal Education in Universities - 廖敦如 Tun-Ju Liao (National Taiwan Normal University, 2009)
現今的教育場域已逐漸向外擴散，範圍不再限於校園內，議題也擴及社會及職場，高等教育希冀能培養出積極參與各種公共事務的學生；而針對大學的通識藝術教育，應該設計什麼課題？活用何種教學方式？讓大學生能夠將藝術學習，內化成一種能力，進而成為一位生活藝術的實踐者，是本研究關切的議題。本研究採用行動研究法，研究目的為：一、發展「行動學習」為教學策略之「社區文化」主題式通識藝術課程；二、進行本課程之實施成效評量。其課程實施結果為：一、「行動學習」的教學策略融入藝術課程中，可引發學生藝術實踐與藝術改革的行動力；二、「社區文化」為議題的藝術課程，可以逐年更換其社區行動場域，透過課程內容深化學生與社區文化的互動；三、透過多元評量機制的建立，可多面相地瞭解學生的學習歷程與學習成效。 The educational field nowadays has been gradually expanding, whose range is not limited to campus anymore, and the issues related have also extended to both society and workplace. Besides, the higher education wishes to foster students to become active in participating in public affairs. In respect of the art liberal education in universities, what courses should be designed and what teaching methods can be applied to enable students to internalize art learning to a kind of ability and further become practitioners of art of living are the issues on which the research concentrates. For this reason, action research is applied with the research purposes of (1) developing a "community culture" with a theme-based general art knowledge course in which "action learning" as a teaching strategy and (2) assessing the performance of this course. The results of implementing this course are: (1) the community action settings of the art courses with "community culture" as the course main issue can be changed every year, and through the course contents the interaction between students and the community culture is to be enhanced; (2) that the teaching strategies of "action learning" are integrated with art courses can encourage students to actually practice and reform art; (3) learning process and performance of the students can be understood in a diversified way via establishing a multiple assessment mechanism.